Surgical consultation in neonates with congenital syphilis - Amanda Munoz; Tabitha Crane; Rajaie Hazboun; Anamika Banerji; Joanne Baerg (Elsevier, 2019)
Objective: The aim was to review the incidence and clinical presentation of neonates with congenital syphilis requiring surgical consultation at a single tertiary neonatal intensive care unit (NICU). Methods: Between 2014 and 2016, all records incorporating congenital syphilis and syphilis during pregnancy were obtained to establish disease incidence. During this time, neonates with congenital syphilis and a pediatric surgery consultation were reviewed. Demographic data, details of surgical consultation, operations and clinical outcomes were recorded. Results: Between 2014 and 2016, cases of maternal syphilis increased from one to five, and congenital syphilis cases ranged from two to ten. In 2016, four (40%) required surgical consultation. Indications for surgical consultation included: (1) obstructive jaundice, (2) abdominal distension with bilious emesis, (3) distension and hematochezia, and (4) possible anorectal malformation. All were diagnosed by rapid plasma reagin test (RPR) and completed a 10-day course of Penicillin G. One neonate with obstructive jaundice underwent surgery to rule out biliary atresia. Three neonates did not require surgical intervention. Conclusion: An understanding of congenital syphilis is imperative for pediatric surgeons. Hepatic and gastrointestinal manifestations may mimic surgical diagnoses in neonates. Keywords: Congenital syphilis, Surgical consults, Neonates, Syphilis in pregnancy